Acute onset clozapine-induced hyperglycaemia: A case report. Issue 2 (11th April 2019) - Kumar, Pradeep; Mishra, Dheerendra Kumar; Mishra, Nimisha; Ahuja, Sunil; Raghuvanshi, Gyanendra; Niranjan, Vijay
Abstract : Clozapine is an atypical antipsychotic which is described to have higher efficacy among all available antipsychotic medications. Clozapine is reserved especially for resistant schizophrenia due to its side effects. Clozapine-induced metabolic syndrome and hyperglycaemia are common long-term side effects and are responsible for increased mortality in patients with schizophrenia. In this case, a patient with resistant schizophrenia was presented with acute-onset hyperglycaemia and delirium with the use of clozapine within a week. Withdrawal of clozapine in the patient led to the improvement in delirium and hyperglycaemia without the use of any hypoglycaemic agent. This case supports the notion that in certain cases clozapine can induce hyperglycemia through possible direct pathophysiological mechanisms within a shorter time frame.